Historia Antigua en diálogo ; Humanidades Digitales e innovaciones metodológicas - Silva, Filipe N.; Bermúdez Lorenzo, Juan Manuel; Pérez González, Jordi (Access archaeology., 2022)
This volume discusses the implications of the adoption of new tools used in the humanities, specifically archaeology, epigraphy and ancient history, without ceasing to respect traditional scientific methods.